Evaluation of CERS2 gene as a potential biomarker for bladder cancer - Aldoghachi, Ahmed Faris; Baharudin, Aminuddin; Ahmad, Umar; Chan, Soon Choy; Ong, Teng Aik; Yunus, Rosna; Abdul Razack, Azad Hassan; Yusoff, Khatijah; Veerakumarasivam, Abhi (Hindawi, 2019)
The ceramide synthase 2 (CERS2) gene has been linked to tumour recurrence and invasion in many different types of cancers including bladder cancer. In this study, the expression levels of CERS2 in bladder cancer cell lines were analysed using qRT-PCR and the protein expression in clinical bladder cancer histopathological specimens were examined via immunohistochemistry. The potential utility of CERS2 as a predictive biomarker of response to oncolytic virotherapy was assessed by correlating the CERS2 mRNA expression to IC50 values of cells treated with the Newcastle disease virus (NDV), AF2240 strain. This study demonstrates that CERS2 is differentially expressed in different types of bladder cancer cell lines and that the siRNA-mediated downregulation of the expression of CERS2 reduces the migratory potential of UMUC1 bladder cancer cells. However, there were no significant correlations between the expression levels of the CERS2 protein with bladder cancer grade/stage or between the IC50 values of cells treated with NDV and CERS2 expression. Although the utility of CERS2 expression may be limited, its potential as an antimigration cancer therapeutic should be further examined.